Tolstoyan Text and Myth of L. N. Tolstoy in Works by I. Ilf and E. Petrov - V. V. Kuryanova (Tsentr nauchnykh i obrazovatelnykh proektov, 2019)
Tolstoyan text in the works by I. Ilf and E. Petrov is considered. The novelty of the research lies in the fact that the study of supertext structures in modern literary studies is primarily focused on topographical texts (St. Petersburg, Crimea, Venice, London, Perm, etc.) while nominal texts (Pushkinsky, Gogolevsky, Chekhovsky) are little studied and the methodology of their study is not clear. The author offers her definition of Tolstoyan text, as well as methods and techniques for studying such text structures. It is argued that the basis of Tolstoyan text is the myth of L. N. Tolstoy. The structure of the Tolstoyan myth is analyzed, its inherent myths (mythological constant ideas) that were created and reproduced by writers-satirists are revealed. To do this, the author analyzes the novels, stories, feuilletons and essays, as well as documentary materials about the life and death of L. N. Tolstoy, which were made public by the end of the 1920s - mid 1930s. Attention is focused on the originality of Tolstoyan text, typical to satirical works. The question of features of perception of the myth about L. N. Tolstoy is raised in the culture of the first third of the 20th century.